Shifts in the spatiotemporal distribution and sources of nitrous oxide in sediment cores from the Bohai Sea and South Yellow Sea - Li, Siqi; Zhen, Yu; Chen, Ye; Mi, Tiezhu; Yu, Zhigang (Marine pollution bulletin, 2023)
N2O is among the most potent greenhouse gases. In this study, we investigated one of the important N2O production hotspots, the continental margins. We looked at N2O spatiotemporal distributions in situ as well as the potential contributions of nitrification and denitrification to N2O production in sediment cores from the Bohai and South Yellow Seas. Real-time PCR and shotgun metagenomics sequencing were used to analyze the microbial communities related to N2O production. The results showed that N2O concentrations roughly decreased with depth—a trend that was consistent throughout the year and showed no significant seasonal variations. When all the research stations along the continental margin were considered, the estuary exhibited the lowest average N2O concentration. Moreover, nitrification was identified as the main process responsible for N2O production in estuary areas. This study demonstrates that spatial, as opposed to temporal, heterogeneity is the primary factor influencing N2O concentration differences in sediments. [Display omitted] •N2O concentrations roughly decreased with depth and showed no significant seasonal variations.•The estuary depicted the lowest average N2O concentration along the continental margin areas.•Nitrification was the main process responsible for N2O production in estuary.•TOC content was the most important environmental factor influencing N2O concentration.